1992
DOI: 10.1017/s0033822200064213
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Dating of Copper-Preserved Organics

Abstract: The small but vital role of 14C dating in archaeometric research is clearly shown in the copper project reported herein. The 14C ages place a time perspective on the “Old Copper Culture Complex,” substantiating early Libby dates that had been questioned. The respective roles of INAA, PGE and Pb isotope work are briefly summarized. A long tradition of heat treatment from Paleoindian stone to Archaic copper is suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 14 publications
2
19
0
Order By: Relevance
“…However, typically perishable fibers will be preserved when found in association with copper-based metal artifacts (Drooker 2004:1; Petersen and Blustain 2004:150). As artifacts such as brass beads, bracelets, and kettles degrade, they produce toxic biocides that limit the deterioration of cloth found in proximity to such copper-rich objects (Beukens et al 1992:892). Unless textiles are deposited in these extraordinary preservation environments, however, acidic soils will promote their decay.…”
Section: Cloth and Colonialismmentioning
confidence: 99%
“…However, typically perishable fibers will be preserved when found in association with copper-based metal artifacts (Drooker 2004:1; Petersen and Blustain 2004:150). As artifacts such as brass beads, bracelets, and kettles degrade, they produce toxic biocides that limit the deterioration of cloth found in proximity to such copper-rich objects (Beukens et al 1992:892). Unless textiles are deposited in these extraordinary preservation environments, however, acidic soils will promote their decay.…”
Section: Cloth and Colonialismmentioning
confidence: 99%
“…Ten years later, a series of papers was published on archaeological and geological copper‐based metal analyses, beginning with the separation of European trade copper from native copper (Hancock et al 1991a,b). This was followed by a paper on radiocarbon dating of organic materials that had been preserved by the copper artefacts with which they were closely associated (Beukens et al 1992); by papers on the analyses of copper‐based metals from archaeological sites in Ontario (Hancock et al 1993a, 1995a–c, 1999b; Fox et al 1995; Pavlish et al 1996, 1998; Anselmi et al 1997; Walker et al 1999), in Quebec (Moreau et al 1994, 1997; Moreau and Hancock 1995, 1996a,b, 1999a,b) and in Nova Scotia (Whitehead et al 1999), in northeastern Canada.…”
Section: Numbers Of Archaeological and Historical Samples Analysedmentioning
confidence: 99%
“…Until recently, the use of copper was attributed to a period commencing about 5.0 ka B.P., but direct dating of the organic materials preserved in archaeological copper artifacts has shown that prehistoric people of the Lake Superior region were working native copper of the Minnesota-Ontario boundary area as early as 7.0 ka B.P. (Beukins et al, 1992). No longer can it be contended that the presence of copper tools indicates a Late Archaic age.…”
Section: Longer-term Pre-nipissing Transgressionmentioning
confidence: 99%